STRUKTUR GEOLOGI BAWAH PERMUKAAN DAERAH KEBUMEN BERDASARKAN ANALISIS POLA ANOMALI GAYA BERAT DAN GEOMAGNET - Subagio Subagio (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The Gravity anomaly pattern of research area is devided into two groups  involving high and low anomalies. The high anomaly dominating at western and eastern area have positive circular pattern, and the value ranges from 90 mgal to 145 mgal. The east and west high anomalies are separated by low anomaly, having negative circular pattern, varies from 52 mgal to 89 mgal, and the low anomaly is located in the central area. The high anomaly patterns might be caused by andesite intrusive rocks in Karangbolong and Kulon Progo High areas, and Pratertier rock in Karangsambung area. Gravity value of Luk Ulo Complex (114 mgal) is lower than the value of intrusive rocks (145 mgal), meanwhile the negative anomaly indicates sedimentary basin. Karangbolong and Kulonprogo high and the basin are seperated by faults, such as Karangbolong and Purworejo Faults respectively. Keywords :  gravity anomaly, positive circular pattern, negative circular pattern, andesite intrusive rock, sedimentary basin, Luk Ulo Pratertier rocks, Karangbolong Fault, Purworejo Fault, Karangbolong High, Kulon Progo High.